Telemonitoring Kadar EC pH dan Suhu Penyehatan Tanah Tercemar Menggunakan Sensor Konduktivitas Berbasis Web - Rahmana Burchan; Farida Arinie Soelistianto; Koesmarijanto Koesmarijanto (Politeknik Negeri Malang, 2020)
Environmental pollution is the most prominent issue today, along with the increase in population, it causes a lot of garbage piles. A chemical reaction that produces certain gases causes the accumulation of solid waste to rot. The aim of this research is to create a web-based soil health telemonitoring system using EC sensors, pH sensors, and the web. The results of pH and EC measurements are taken and entered into a database and will be displayed on a web page. The Wemos D1 Mini microcontroller will process the signal read by the sensor and display it on the LCD and Web pages in real time. The results of the application of the system are carried out by plugging the two sensors into the soil to be measured, the results of the data that I took on this land with more colomite were the average EC and the pH on the soil was higher than the soil that was not dominated or had little domination due to the soil that was given dolomite. more will increase the EC and pH of the soil. Based on the results of tests carried out by the EC Soil Sensor and the temperature here can detect soil conductivity with an average value close to 400 µs / cm and an average temperature close to 24-26 ° C because this sensor has calibrated automatically, the pH sensor can detect the pH on the soil evenly 0% error rate.